Generation and verification of optical vortices with controlled phase based on coherent beam combining. (22nd September 2022) - Luo, Hao; Yang, Kaibo; Li, Peng; Wen, Feng; Gu, Yuzong; Wu, Zhenkun
Abstract: Optical vortices (OVs) with controllable orbital angular momentum (OAM) distributions have potential applications in optical communication and optical manipulation. However, the source of optical vortices with segmented phase gradients generated by existing methods can be used only at a short distance because of their low power. In this study, based on coherent combining technology, we proposed a method to generate a controlled-phase optical vortex (COV). Compared with traditional OVs, the magnitude and direction of the local OAM of the COV are controllable. The transmission characteristics of the COV in free space were numerically examined using a split-step Fourier transform algorithm. We theoretically and experimentally proved the feasibility of the coherent combining technology to generate an COV and proved that it has the properties of non-diffraction and self-healing.